Ecophysiological aspects of guava (Psidium guajava L.). A review - Fischer, Gerhard; Melgarejo, Luz Marina (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
Guava, because of its ability to grow in tropical and subtropical climates, has been introduced to some 60 low-latitude countries. It is adapted to a temperature range between 15 and 30°C. Outside this range, the effect of lower or higher temperatures reduces fruit set, while night temperatures of 5 to 7°C stop growth. Additionally, low temperatures hinder production, causing flowers to fall or increasing the fruit development cycle, up to 220 days. When estimating the cardinal temperatures of development, the minimum threshold temperature was 10.9°C, the optimum temperature was 17.3°C, and the maximum threshold temperature was 51.2°C. The guava tree adapts well to altitudes between 0 and 2,000 m a.s.l. in Colombia; however, there is a high genotype×environment interaction for production and quality characteristics in fruits with respect to the orchard elevation. Radiation >2,000 µmol photons m-2 s-1 decreased the fruit ascorbic acid content. An important ecophysiological factor in guava is water, and crops require between 1,000 to 2,000 mm year-1. It withstands waterlogging for several days, but excess precipitation and atmospheric humidity decrease fruit quality considerably. However, this tree is classified as moderately drought-tolerant to stress from water deficits, affecting flowering and fruit set. It is also moderately tolerant to salinity, depending on the variety, supporting electrical conductivities up to 1.5-1.8 dS m-1. Generally, guava can be cultivated in a wide range of tropical and subtropical areas, where it is preferred because of its high nutritional and medicinal contents and its aptitude for transport and handling.